Regional SDG Performance in Bulgaria and Romania: Poverty, Education, and Decent Work - Alexandra-Nicoleta Ciucu (Durnoi); Kosyo Stoychev; Camelia Delcea; Vanesa Mădălina Vargas; Carmen Păuna (Amfiteatru Economic)
Sustainable development emerged from the desire of global authorities to ensure a balance between economic, ecological, and social plans, thus showing that the interest in economic growth must be mediated by ensuring a decent living for all inhabitants of the planet. The current research analysed the regional performances recorded by two EU member states located in the south-east of Europe, respectively Bulgaria and Romania. For the 14 identified regions, a number of 10 indicators have been identified that illustrate the targets of three Sustainable Development Goals (SDG1 - No poverty, SDG4 - Quality education, and SDG8 - Decent work and economic growth). The study began with a descriptive analysis, through which the situation of each individual indicator was detailed, and ended with a TOPSIS analysis in order to determine the regional ranking based on the identified performances of the investigated indicators. In most of the studies that were carried out on the progress of the EU member states in achieving the SDGs, information was presented at the country level, without deepening the study at a regional level. The current research involved studying the results of macro-regions because significant discrepancies between them were identified. Both the results and the conclusions that were provided should attract the attention, first of all, of the decision-makers in both countries, in order to correct the current situation because the deadline for reaching the targets proposed by the 2030 Agenda is fast approaching and, according to the current situation, there is a possibility that the objectives will not be met.